2012
DOI: 10.5139/ijass.2012.13.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angles of Attack and Throttling Conditions on Supersonic Inlet Buzz

Abstract: A series of numerical simulations are carried out to analyze a supersonic inlet buzz, which is an unsteady pressure oscillation phenomenon around a supersonic inlet. A simple but efficient geometry, experimentally adopted by Nagashima, is chosen for the analysis of unsteady flow physics. Among the two sets of simulations considered in this study, the effects of various throttling conditions are firstly examined. It is seen that the major physical characteristic of the inlet buzz can be obtained by inviscid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As seen, up to now no reliable prediction method of intake buzz has been developed through the analytical investigations. Therefore, numerical [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] or experimental [8,13,23,25,27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] methods are often used to study the buzz onset as well as its frequency and amplitude for various flow conditions. It seems that the work done by Trapier et al [18] is the most complete study among the numerical investigations because the flow separation is the key phenomenon in the buzz onset according to the Ferri [5] and Dailey [6] criteria, and to the authors' knowledge, this study is the only numerical investigation that uses the large-eddy simulation approach (detached-eddy simulation turbulence model) and three-dimensional grid to study buzz.…”
mentioning
confidence: 99%
“…As seen, up to now no reliable prediction method of intake buzz has been developed through the analytical investigations. Therefore, numerical [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] or experimental [8,13,23,25,27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] methods are often used to study the buzz onset as well as its frequency and amplitude for various flow conditions. It seems that the work done by Trapier et al [18] is the most complete study among the numerical investigations because the flow separation is the key phenomenon in the buzz onset according to the Ferri [5] and Dailey [6] criteria, and to the authors' knowledge, this study is the only numerical investigation that uses the large-eddy simulation approach (detached-eddy simulation turbulence model) and three-dimensional grid to study buzz.…”
mentioning
confidence: 99%
“…Similarly to the work of Soltani and Farahani [62], Namkoung et al [100] noticed that buzz frequency does not change dramatically with AOA for a constant throttle ratio of 0, but the shock structure varies abruptly, in the sense that it becomes asymmetric. Looking at the induced distortion from the asymmetry of the flow, the study shows that, as the angle of attack increases from 3 to 10 • , the shock structure and flow physics appear asymmetric.…”
Section: Effect Of Angle Of Attackmentioning
confidence: 72%
“…(Saha, Singh, and Seshadri 2007) Namkoung et al 2012numerically investigated the effects of AOA on a supersonic axisymmetric intake. They reported that by increasing the AOA from 3º to 10º, distortion increased up to 30% which is believed to be due to the axisymmetric (or three-dimensional) shock structures affected by the AOA variation (Namkoung et al, 2012). Trefiny et al (2014) experimentally investigated the effects of angle of attack on a supersonic ramped inlet equipped with an elliptical cowl and reported an abrupt decrease in both total pressure recovery and mass flow ratio (Trefny et al, 2014).…”
Section: Aipmentioning
confidence: 99%